Analysis of Aerodynamics Regimes in Residential Building Apartments - V. D. Sizov; V. D. Akeliev; A. I. Arestovich; S. G. Bykovsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2003)
Methodology on analysis of ventilation conditions in civil buildings has been elaborated on the basis of studying thermal and material balances of internal apartment volumes and hydraulic losses for various regimes of air flow movement. The results of numerical investigations which illustrate the methodology are given in the paper. Plots have been constructed and they make it possible to assess the conditions of air flow movement in the apartments. The methodology is applicable for analysis of ventilation conditions in industrial buildings.